Schistosoma mansoni and soil-transmitted helminthic infections and associated factors among pregnant women in Jimma Town, Southwest Ethiopia - Abebaw Tiruneh; Endalew Zemene; Biru Abdissa Mizana; Daniel Dana; Hundaol Girma; Mio Ayana; Zeleke Mekonnen (BMC, 2024)
Abstract Background Schistosomiasis and soil-transmitted helminth (STH) infections occurring during pregnancy may pose adverse health consequences to the mother and the developing baby. This study aims to determine the prevalence of Schistosoma mansoni and STHs, and their association with adverse birth outcomes among pregnant women in Jimma Town. Methods A cross-sectional study involving 314 pregnant women was conducted in Jimma Town, Southwest Ethiopia. The pregnant women were recruited from selected public health facilities during their antenatal care (ANC) visits from August to December 2021. Data on demographic characteristics and factors associated with S. mansoni and STH infections were collected using a pretested questionnaire. Moreover, during the third trimester, stool specimen of each pregnant woman was examined using Kato-Katz technique, and hemoglobin was measured using a HemoCue analyzer. Data on adverse birth outcomes were collected during delivery. Data were analyzed using STATA-MP_12 (StataCorp., TX, USA). Results The overall prevalence of intestinal helminthic infections was 26.1%. Soil-transmitted helminths and S. mansoni were detected in 20.4% (95%CI: 15.9-24.8) and 5.7% (95%CI: 3.2-8.3) of the pregnant women, respectively. The magnitude of low birth weight was 6.4%, higher in those with late-term delivery and maternal anemia (p < 0.05). Maternal anemia was also associated with post-partum bleeding (p < 0.05). Pregnant women who carry out laundry activities in the river were significantly more infected by S. mansoni (AOR 10.7, 95% CI: 2.2-51.9). Conclusions This study sheds light on the burden of maternal STH and S. mansoni infections in Jimma Town. A quarter of the pregnant women were infected with STHs and S. mansoni. It is recommended that pregnant women in the area avoid washing clothes in the river to reduce the risk of S. mansoni infection. Screening for intestinal parasitic infections should be conducted for pregnant women living in endemic areas during their ANC follow-up.